Prostaglandins in Superovulation Induced Bovine Follicles During the Preovulatory Period and Early Corpus Luteum - Berisha, Bajram; Rodler, Daniela; Schams, Dieter; Sinowatz, Fred; Pfaffl, Michael W. (Frontiers in Endocrinology, 2019)
The aim of this study was to characterize the regulation pattern of certain prostaglandin family members in the bovine follicles during periovulatory period and early corpus luteum (CL). Ovaries containing preovulatory follicles or CL were collected by transvaginal ovariectomy (n=5 cows/group), and the follicles were classified: (I) before GnRH administration; (II) 4h after GnRH; (III) 10h after GnRH; (IV) 20h after GnRH; (V) 25h after GnRH, and (VI) 60h after GnRH (early CL). In these samples, the concentrations of progesterone (P4), estradiol (E2), prostaglandin F2alpha (PTGF) and prostaglandin E2 (PTGE) were investigated in follicular fluid (FF) by validated EIA. The prostaglandin receptors (PTGFR, PTGER2, and PTGER4), and enzymes cyclooxygenase 2 (COX-2), PTGF synthase (PTGFS) and PTGE synthase (PTGES) were quantified by RT-qPCR. The tissue localization of COX-2 and PTGES were investigated by established immunohistochemistry. The FF concentration of E2 was high in the follicle group before and during luteinizing hormone (LH) surge, followed by a significant downregulation afterwards. In contrast the concentration of P4 was very low before LH surge followed by a maximal level during ovulation. The mRNA expression of COX-2 increased 4h after GnRH and again 20h after GnRH, followed by a significant decrease after ovulation (early CL). The mRNA of PTGFS in follicles before GnRH was high followed by a continuous and significant downregulation afterwards. In contrast, PTGES mRNA was low and increased rapidly in follicles 20h after GnRH and remained high afterwards. The mRNA of PTGFR, PTGER2 and PTGER4 in follicles before GnRH was high, followed by a continuous and significant down regulation afterwards and significant increase only after ovulation (early CL). The concentration of PTGF and PTGE in FF was low before GnRH application, increased continuously and significantly 20h after GnRH and displayed a further rapid increase around ovulation. Immunohistochemically, the granulosa cells showed strong staining for COX-2 and PTGES in follicles during periovulation and in granulosa-luteal cells of the early CL. In conclusion, our results indicate that the examined bovine prostaglandin family members are involved in the local mechanisms regulating final follicle maturation and ovulation during the folliculo-luteal transition and CL formation.